The Concept of The Management of Body Functions and Their Properties. Organism and environment - Utepbergenov Amangeldi Kutlimurotovich (International Journal on Human-Computing Studies, 2021)
An organism is a unit of the organic universe that can live independently, be self-governing, and respond to various changes in the external environment as a whole. ” The body should be thought of as a whole, not as a collection of parts or individual cells. All the organs, systems, and functions of a complex organism are constantly interacting with one another